Cancer-Associated Fibroblasts Neutralize the Anti-tumor Effect of CSF1 Receptor Blockade by Inducing PMN-MDSC Infiltration of Tumors - Kumar, Vinit; Donthireddy, Laxminarasimha; Marvel, Douglas; Condamine, Thomas; Wang, Fang; Lavilla-Alonso, Sergio; Hashimoto, Ayumi; Vonteddu, Prashanthi; Behera, Reeti; Goins, Marlee A; Mulligan, Charles; Nam, Brian; et al. (Cancer cell, 2017)
Tumor-associated macrophages (TAM) contribute to all aspects of tumor progression. Use of CSF1R inhibitors to target TAM is therapeutically appealing, but has had very limited anti-tumor effects. Here, we have identified the mechanism that limited the effect of CSF1R targeted therapy. We demonstrated that carcinoma-associated fibroblasts (CAF) are major sources of chemokines that recruit granulocytes to tumors. CSF1 produced by tumor cells caused HDAC2-mediated downregulation of granulocyte-specific chemokine expression in CAF, which limited migration of these cells to tumors. Treatment with CSF1R inhibitors disrupted this crosstalk and triggered a profound increase in granulocyte recruitment to tumors. Combining CSF1R inhibitor with a CXCR2 antagonist blocked granulocyte infiltration of tumors and showed strong anti-tumor effects.